2021
DOI: 10.1002/aelm.202100590
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Orbit Torque and Interfacial Dzyaloshinskii–Moriya Interaction in Heavy Metal/Ferrimagnetic Insulator Deposited by Magnetron Sputtering

Abstract: Ferrimagnetic insulators (FMIs) have abundant advantages for the application in spintronic devices, which have attracted intensive studies. However, in most previous studies on heavy metal (HM)/FMI bilayers, the FMI layers are deposited by pulsed laser deposition (PLD), and the HM layers are deposited by magnetron sputtering. This will cause the interfacial contamination due to the inevitable vacuum breaking, and then significantly affect the spin‐orbit torque (SOT) generation and the Dzyaloshinskii–Moriya int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…For instance, Ye et al reported a value of ξ DL = 0.029 in a Pt/ TmIG bilayer. 33 Avci et al reported a value of ξ DL ≈ 0.01 in a Pt/TmIG bilayer. 27 Chen et al reported a value of ξ DL = 0.011 in a Pt/Tb 3 Fe 5 O 12 (TbIG) bilayer.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…For instance, Ye et al reported a value of ξ DL = 0.029 in a Pt/ TmIG bilayer. 33 Avci et al reported a value of ξ DL ≈ 0.01 in a Pt/TmIG bilayer. 27 Chen et al reported a value of ξ DL = 0.011 in a Pt/Tb 3 Fe 5 O 12 (TbIG) bilayer.…”
mentioning
confidence: 97%
“…Argon gas was applied for the deposition. The detail of the fabrication is described in our previous report . After cooling down to room temperature, Pt and Ta layers were deposited subsequently on the TmIG surface without breaking the vacuum.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One prominent category within FMI features ferrimagnetic rare-earth iron garnet, renowned for its low Gilbert damping, a Néel temperature exceeding RT, and robust perpendicular magnetic anisotropy (PMA) induced by magnetoelastic anisotropy, [5][6][7] which ensures low energy consumption and high-speed response in spintronic devices, [8][9][10][11][12] with Tm 3 Fe 5 O 12 (TmIG) being the most extensively studied among them. It has been seamlessly integrated into Pt/TmIG heterostructures, 8,[13][14][15] demonstrating the anticipated spin-orbit torques (SOTs), which offers an efficient and scalable method for electrically manipulating the magnetization of TmIG. Nevertheless, the switching of TmIG by SOT necessitates an external in-plane (IP) magnetic field (H x ) parallel to the longitudinal current direction, thereby impeding the progress of TmIG into practical applications.…”
mentioning
confidence: 99%